ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA BERDASARKAN LANGKAH-LANGKAH POLYA PADA SISWA SMP N 1 SIPIROK - Lisna Agustina; Kholid Umar (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
The purpose of this study was to analyze students 'mathematical problem-solving abilities based on Polya's steps that could improve students' mathematical problem-solving abilities in class VIII of SMP Negeri 1 Sipirok. Research data obtained from the analysis of student answer sheets based on indicators of problem solving ability, observation sheets, and student activity sheets. This type of research is a quasi-experimental design with a pretest posttest design. To see improvement in every aspect of problem solving ability as well as all aspects of students' mathematical problem solving abilities, an N-Gain test and a t test were performed. The main results of this study are the students 'mathematical problem solving abilities based on Polya's steps better than the students' problem solving abilities with normal learning.